Pregnancy and neonatal outcomes of assisted pregnancies in a low-middle income country in South Asia - Sachith Mettananda; Himali Herath; Ranod Madushith; Tiran Dias; Rasika Herath; Sampatha Goonewardena; Dhammica Rowel; Abner Elkan Daniel; Susie Perera (BMC Pregnancy and Childbirth)
Abstract Background Assisted reproductive techniques are increasingly used to achieve fertility in developing countries in South Asia. However, the data on the outcome of assisted pregnancies are sparse. This study aims to evaluate the pregnancy, delivery and neonatal outcomes and complications of assisted pregnancies in Sri Lanka, a low-middle-income country in South Asia. Methods We performed a secondary analysis of the data of the island-wide multi-centre Sri Lanka Birth Weight Study, which recruited all live-born newborns in 13 hospitals covering 20% of all births in the country from 01 August to 30 September 2023. Data on socio-demographic background, type of conception, pre-pregnancy medical, obstetric and delivery complications and immediate neonatal outcomes were collected by interviewing mothers and perusing patient records. Maternal age-, multiple births- and prematurity-adjusted odds ratios were determined by logistic regression analysis. Results Of the 8992 pregnancies, 8900 (99.0%) were spontaneous conceptions. The assisted pregnancy rate was 1.0%, with 52 intra-uterine insemination and 40 in-vitro fertilisation pregnancies. The mean ages of mothers who had intra-uterine insemination (31.2 years) or in-vitro fertilisation (38.7 years) were significantly (p < 0.001) higher than the mothers who had spontaneous conceptions (28.6 years). Pregestational diabetes (p = 0.003) and hypothyroidism (p < 0.001) were significantly higher in the assisted pregnancy group compared to the spontaneous conceptions. Regarding pregnancy complications, gestational diabetes (p = 0.001) was higher in in-vitro fertilisation pregnancies and urinary tract infection (p < 0.001) was higher in intra-uterine insemination pregnancies. The multiple births (6.4% vs. 1.2%, p < 0.001) and caesarean section (77.2% vs. 41.8%, p < 0.001) rates were significantly higher among the assisted pregnancy group compared to spontaneous conceptions. Neonates born following assisted pregnancies were significantly more likely to be premature (p < 0.001), low birth weight (p < 0.05), admitted to neonatal intensive care units (p < 0.001) and die within the first day of life (p < 0.05) compared babies born following spontaneous conceptions. Conclusions The assisted pregnancy rate in this study was 1%, and assisted pregnancies were more common among women with pregestational diabetes and hypothyroidism. Gestational diabetes and urinary tract infections were more frequent in assisted pregnancies. Neonates born following assisted pregnancies reported significant morbidity and mortality compared to spontaneous conceptions.